2019
DOI: 10.1016/j.ghir.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The insulin-like growth factor-I receptor stimulating activity (IRSA) in health and disease

Abstract: Determination of true IGF-I bioactivity in serum and other biological fluids is still a substantial challenge. The IGF-IR Kinase Receptor Activation assay (IGF-IR KIRA assay) is a novel tool to asses Responses to the Reviewers of GHIR-D-19-00026-Janssen et al.-The Insulin-like Growth Factor-I Receptor Stimulating Activity (IRSA) in Health and Disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…This is consistent with the ndings by Cohen et al [42] who reported that IGFBP-2 was found in prostate epithelial cell-conditioned medium. Studies from both in vivo and in vitro models suggest that IGFBP-2 exerts inhibitory effects on IGF-mediated functions [43]. Hence, it is likely that SP IGFBP-2 may not induce any meaningful inhibitory effects on IGF-I and IGF-II actions in affecting sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the ndings by Cohen et al [42] who reported that IGFBP-2 was found in prostate epithelial cell-conditioned medium. Studies from both in vivo and in vitro models suggest that IGFBP-2 exerts inhibitory effects on IGF-mediated functions [43]. Hence, it is likely that SP IGFBP-2 may not induce any meaningful inhibitory effects on IGF-I and IGF-II actions in affecting sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, influence of these IGFBP protease inhibitors on IGFBP/protease balance appears less important in interstitial fluids [41], rendering protease activity unopposed [41]. Consistent with this possibility, IGF-IR stimulating activity, as assessed by IGF-IR kinase receptor activation assay is increased in interstitial fluids compared to serum [45].…”
Section: Biology Of Insulin-like Growth Factor (Igf) Family and Theirmentioning
confidence: 90%
“…Physical activity is very important to do because it can increase body strength. The most important thing is increased activity can increase insulin receptors to absorb and use glucose properly [19,20]. Insulin receptors are important for people with DM because they can improve quality of life [21,22].…”
Section: Discussionmentioning
confidence: 99%